The Impact of the Stadium in the Supporter’s Consumption: How Does the Frequency at The Stadium Boosts the Demand for the Clubs’ - Fleury, Fernando A. (2014)
The aim of this study is to investigate the relationship between the presence of supporter in the stadium, which demonstrates the supporter’s involvement with his soccer club, and its influence on the purchase of official products of the 12 largest Brazilian brands of soccer clubs. In this research, it was collected information from 1,296 supporters who responded to a questionnaire with 22 questions. It was defined as involvement with their soccer club the frequency this supporter goes to the stadium. In order to determine the consumption relationship it were used variables such as frequency of purchase of official products, the annual amount spent on such products, favorite venue to purchase and assortment of the products mix. For the supporters buying preferences analysis, it was applied the technique of correspondence analysis (Anacor). As a result, we can point out that the supporters’ loyalty, driven by the relationship marketing, is one of the catalysts for increasing the soccer clubs revenue, since the higher the products and average tickets purchase frequency, the more this frequency is associated with a higher number of attendance to the stadium, as well as the variety in the mix of products acquired by the supporter. In this sense, the work points to the importance of building a long term relationship which goes beyond the emotional bond with the club, reaching the brand products consumption.